Thermal distribution analysis of rice weevil disinfestation using microwave heating treatment - Maliki Ibrahim; Rosemizi Abd Rahim; Junita Mohd Nordin; Siti Zulaika Abdul Nyzam; Muhammad Thaqif Abdullah (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents an analysis of a microwave heating thermal distribution in the rice weevil disinfestation treatment. The sample of rice and rice weevil has been heated by microwave and the infrared thermal camera has been used to capture the heating distribution. The analysis of the rice and the rice weevil condition due to electromagnetic energy exposure is presented. There are three stages of the microwave heating has been taken in the analysis i.e. 10, 20, 30 seconds exposure period at 100W of energy.  Found that the treatment of rice weevil disinfestation using microwave energy is promising in the future, but needs a lot of improvement to be studied. The beauty of using microwave energy for rice weevil disinfestation is not only the rice weevil can be killed, but even its eggs or larvae inside the rice kernel will be killed before it hatches.